CERVICAL CANCER: TRIGGERING FACTORS - Krutikova, E.I. (World of Medicine and Biology, 2018)
The relevance of the study of cervical carcinogenesis is due to the high incidence of the papillomavirus infection among young women (up to 95%), which oncogeneicity has been proven to date. The purpose of the present study was the analysis of the findings of recent studies on the triggers of cervical cancerogenesis. The author emphasizes the findings of immunocytochemical study of cervical cells for the detection of toll-like receptors (TLR 3,4,7,8), nitric oxide synthase (iNOS), the NF-kB p 65 transcription factor, which are the controllers of the cellular cycle. The dysfunction of these enzymes leads to carcinogenesis. The analyzed publications indicated that the TLR 3, 4, 7, 8, iNOS and NF-kB p 65 expressions in the epithelial cells of cervical cancer significantly exceeded the one in the benign HPV-cells and disease-free specimens (р
Keywords: cervical cancerogenesis; toll-receptors; nitric oxide synthase; folates; papillomavirus